Dari Mukjizat ke Pemerataan: Kajian Ekonomi Petani Indragiri Hulu 1980—2010 - Zaiyardan Zubir (Lembaran Sejarah, 2016)
Indonesian economic development in the Soeharto’s New Order brought a miracle and absolute poverty. In the case of Indragiri Hulu’s community farmer, that miracle looked up from the massive development oil palm plantation as well as the rapid growth of cities and liveliness of population around the plantation area. While absolute poverty was seen from the deprivation and deforestation of hutan lindung (protected forests), hutan larangan (prohibited forests), hutan adat (customary forests), and hutan ulayat also the expropriation of inhabitan’s land without compensation. Moreover, oil palm plantations changed the status of the surrounding community (from landowners to be labourers), eliminated their additional income, then caused bareforests and flood every rainy.